Energy Management Systems for Residential Buildings With Electric Vehicles and Distributed Energy Resources - Sohaib Rafique; Mohammad Jahangir Hossain; Mohammad Sohrab Hasan Nizami; Usama Bin Irshad; Subhas Chandra Mukhopadhyay (IEEE Access, 2021)
This paper proposes two electric energy management systems (EMSs) in the context of a grid-connected residential neighbourhood with electric vehicles (EVs), battery storage, and solar photovoltaic (PV) generation. The EMSs were developed to minimize the cost of electricity whilst having no impact on routine individual energy needs and travel patterns. The EMSs were evaluated using common sets of real data with the aim to compare the effectiveness of a centralized EMS with decentralized EMS. The models also accounted for the battery capacity degradation and the associated costs. Simulation studies and numerical analyses were presented to validate the effectiveness of the proposed EMSs considering a high-density residential building in Sydney, Australia. The simulation results indicate that the centralized EMS is more effective compared to the decentralized EMS in terms of cost savings. It is also observed that the energy management strategies significantly reduce the energy drawn from the grid compared to un-optimized energy management schemes.